The importance of industrial engineering in small & medium industries :a time study in manufacturing industry - Gan, Kiat Yong (2007)
In this thesis, the knowledge on implementation of IE is studied theoretically through a time study in SMI. The study is to find the standard times of the employee and find out a solution to maximum the labor efficiency based on the knowledge of IE and the time study results. This study was mainly carried out by preparing the letter to industry, industry visit, process listing, data collection, analysis of the data, result and discussion of the data, and conclusion. In this time study, WS Food Trading is a small industry with the limited and traditional ways of management. The study will show the data collection procedures from parts division to standard get. Study show that the WS food trading doesn't have the knowledge about the standard times getting and the knowledge on implementation of IE for the industry. So after the study, it is hope that the results analysis and the solution came out will contributed for the company.